Mekanisme Kerja Otak dan sistem saraf: Pengaruhnya terhadap Proses Pembelajaran Siswa Sekolah Dasar: How the Brain and Nervous System Work: Their Impact on the Learning Process of Elementary School Students - Muhammad Hifni Fajriani Iip; Iis Kholisoh; Eka Ulfiani (Sumule Indonesia Publishing, 2024)
This study aims to understand the working mechanisms of the brain and nervous system of elementary school children and their influence on learning and cognitive development. The brain and nervous system play an important role in regulating mental and physical activities such as perception, memory, attention and motor skills. Children in primary school are still experiencing significant brain development that affects their ability to receive, process and store information. This study uses a descriptive approach through literature research and direct observation of students' neurological responses during various learning activities. The results show that the relationship between brain function, the nervous system, and the learning environment plays an important role in improving students' conceptual understanding and practical skills. The significance of this research is expected to help teachers and educators develop more effective learning methods while still paying attention to the neurological factors that play a role in the learning process of elementary school students.